2014
DOI: 10.1111/1574-6941.12295
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the cultivable human gut microbiome involved in gluten metabolism: isolation of microorganisms with potential interest for coeliac disease

Abstract: Gluten, a common component in the human diet, is capable of triggering coeliac disease pathogenesis in genetically predisposed individuals. Although the function of human digestive proteases in gluten proteins is quite well known, the role of intestinal microbiota in the metabolism of proteins is frequently underestimated. The aim of this study was the isolation and characterisation of the human gut bacteria involved in the metabolism of gluten proteins. Twenty-two human faecal samples were cultured with glute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
141
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(150 citation statements)
references
References 30 publications
4
141
0
5
Order By: Relevance
“…Indeed, gluten-degrading bacteria have been isolated from the gastrointestinal tracts of humans and pigs (21)(22)(23)(24)(25). Previously, it was shown that Lactobacillus rhamnosus GG improves the intestinal permeability of Caco-2 cells when exposed to gliadin peptides (26).…”
mentioning
confidence: 99%
“…Indeed, gluten-degrading bacteria have been isolated from the gastrointestinal tracts of humans and pigs (21)(22)(23)(24)(25). Previously, it was shown that Lactobacillus rhamnosus GG improves the intestinal permeability of Caco-2 cells when exposed to gliadin peptides (26).…”
mentioning
confidence: 99%
“…Recently, it was shown that GFD treatment signiicantly altered proportions of these bacterial groups and that restoration of normal bacterial lora took many months and possibly years [14,15]. It was also shown that increased presence of some of the bacterial species involved in gluten metabolism leads to enteritis [13]. Our group recently demonstrated that Streptococcaceae and Lactobacillaceae families were enriched in GS rhesus macaque model of CD, while Coriobacteriaceae predominated in healthy animals [14].…”
Section: Composition Of Host Gut Microbiome and Ncgs/cdmentioning
confidence: 92%
“…It has been reported that bacteria involved in gluten metabolism predominantly belong to phylum Firmicutes, in particular, those from the genus Lactobacillus, followed by Streptococcus, Staphylococcus, and Clostridia [13,14]. Recently, it was shown that GFD treatment signiicantly altered proportions of these bacterial groups and that restoration of normal bacterial lora took many months and possibly years [14,15].…”
Section: Composition Of Host Gut Microbiome and Ncgs/cdmentioning
confidence: 99%
See 1 more Smart Citation
“…At various levels of the digestive tract bacteria forming the intestinal flora is different e.g. colon is dominated by Firmicutes, Bacteroidetes and Actinobacteria [64,65]. The composition of the intestinal microbiome depends on the diet [65,66,67], stress, suffered infections, the hygienic condition and the use of drugs, including antibiotics [68].…”
Section: The Importance Of the Intestinal Microbiomementioning
confidence: 99%